1976
DOI: 10.1007/bf01972201
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of prostaglandin synthesis in vivo by nonsteroid anti-inflammatory drugs: Evidence for the importance of pharmacokinetics

Abstract: A variety of acidic and non-acidic compounds are potent inhibitors of prostaglandin (PG) synthesis in vitro. However, only a few, namely the acidic nonsteroid anti-inflammatory drugs (NSAID) are useful anti-inflammatory analgesics in the clinic. Since inhibition of PG-synthesis is believed to be the main target of NSAID in inflammation this superiority of acidic compounds remains unexplained. We have considered that one explanation could be that only acidic NSAID appear in high concentrations in inflamed tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The analysis also supports the observation that NSAIDs with higher pKa's exhibit greater antiinftammatory potency, as already suggested by Brune et al [87]. It has been hypothesized that increasing the pKa of NSAIDs will increase their unionized concentrations in the extracellular fluid, which in turn will increase the diffusion of drug molecules to intracellular sites of action [6].…”
Section: Discussionsupporting
confidence: 70%
“…The analysis also supports the observation that NSAIDs with higher pKa's exhibit greater antiinftammatory potency, as already suggested by Brune et al [87]. It has been hypothesized that increasing the pKa of NSAIDs will increase their unionized concentrations in the extracellular fluid, which in turn will increase the diffusion of drug molecules to intracellular sites of action [6].…”
Section: Discussionsupporting
confidence: 70%
“…In addition, this drug has been shown to block the nuclear translocation of the transcription factor, nuclear factor kappa beta (NF-κβ), which mediates cytokine production including IL-1β, TNFα and IL-6 (Scheuren et al 1998). A potentially important physical property of ibuprofen is its tendency to partition into low pH compartments, such as local areas of inflammation (Brune and Lanz 1985; Brune et al 1976). The steroid, dexamethasone, operates via nuclear receptors to block the cascade of cytokine synthesis and release.…”
Section: Effect Of Anti-inflammatory Drugs On Chemoreceptor Adaptamentioning
confidence: 99%
“…Brune et al (1976) have suggested that pKa and plasma protein binding characteristics may predict AI activity for cyclooxygenase inhibitors. Although a clear-cut reason for this phenomenon is not known, it can be speculated that highly bound AI drugs reach inflarnmed tissue sites to exert their pharmacologic effect through the extravasation of proteins resulting from a change in capillary permeability at the site of inflammation.…”
Section: Pharmacokinetic Pharmacodynamic and Toxicity Relationsidpsmentioning
confidence: 99%